Agathisflavone as a Single Therapy or in Association With Mesenchymal Stem Cells Improves Tissue Repair in a Spinal Cord Injury Model in Rats - do Nascimento, Ravena P.; de Jesus, Lívia B.; Oliveira-Junior, Markley S.; Almeida, Aurea M.; Moreira, Eduardo L. T.; Paredes, Bruno D.; David, Jorge M.; Souza, Bruno S. F.; de Fátima D. Costa, Maria; Butt, Arthur M.; Silva, Victor Diogenes A.; Costa, Silvia L. (Frontiers in Pharmacology, 2022)
Agathisflavone is a flavonoid with anti-neuroinflammatory and mielinogenic properties, being also capable to induce neurogenesis. This study evaluated the therapeutic effects of agathisflavone – both as a pharmacological therapy administered in vivo and as an in vitro pre-treatment aiming to enhance rat mesenchymal stem cells (r)MSCs properties - in a rat model of acute spinal cord injury (SCI). Adult male Wistar rats (n=6/group) underwent acute SCI with an F-2 fogarty catheter and after 4 h were treated daily with agathisflavone (10 mg/kg ip, for 7 days), or administered with a single i.v. dose of 1x10^6 rMSCs either, unstimulated cells (control) or pretreated with agathisflavone (1 µM, every 2 days, for 21 days in vitro). Control rats (n=6/group) were treated with a single dose of methylprednisolone (MP, 60 mg/kg ip). BBB scale was used to evaluate the motor functions of the animals; after 7 days of treatment, the SCI area was analyzed after H&E staining, and RT-qPCR was performed to analyze the expression of neurotrophins and arginase. Treatment with agathisflavone alone or with of 21-days agathisflavone - treated rMSCs was able to protect the injured spinal cord tissue, being associated with increased expression of NGF, GDNF and arginase, and reduced macrophage infiltrate. In addition, treatment of animals with agathisflavone alone was also able to protect injured spinal cord tissue and to increase expression of neurotrophins, modulating the inflammatory response. These results support a pro-regenerative effect of agathisflavone that holds developmental potential for clinical applications in the future.